(untitled) (Open Academia: Journal of Scholarly Research, 2023)
The work studied occupational diseases during oil refining, the mechanism of action of oil and its products on the human body. The characteristics of air pollution in the working area are given. The symptoms of poisoning from inhaling high concentrations of gasoline vapors have been widely reported.